Efficacy and Safety of Sarilumab in COVID-19: A Systematic Review - Chamlagain, Rajan; Shah, Sangam; Sharma Paudel, Basanta; Dhital, Roman; Kandel, Bipin (Interdisciplinary Perspectives on Infectious Diseases, 2021)
Background. It has been found that there is overactivation of immune response in patients with COVID-19. Several studies are going on to assess the role of immunomodulation. IL-6 antibodies such as tocilizumab have been found to have efficacy in the treatment of COVID-19. We aim to assess the role of sarilumab in the treatment of COVID-19 through this review. Main Body. Functional outcomes were assessed on the basis of PaO2/FiO2 ratio, mortality, and ventilation. Adverse events of studies were also noted. Five studies were included in the study. There was improvement in PaO2/FiO2 ratio, reduction in the mortality of the patients, and less number of patients were on ventilation, but there were no significant differences among the comparison and sarilumab group. Sarilumab did not have notable adverse events and can be considered a safe drug. Conclusion. Sarilumab is a safe drug with good clinical outcomes in patients with COVID-19 and, hence, could be used as an alternative regimen for the treatment. Further prospective studies exploring the relations with baseline biomarkers of inflammation commonly measured such as C-reactive protein and IL-6 would be necessary for a correlation with the treatment.